Comparison of Antiplatelet Effects of Phenol Derivatives in Humans - Hrubša, Marcel; Alva, Raúl; Parvin, Mst Shamima; Macáková, Kateřina; Karlíčková, Jana; Fadraersada, Jaka; Konečný, Lukáš; Moravcová, Monika; Carazo, Alejandro; Mladěnka, Přemysl (Biomolecules, 2022)
Flavonoids are associated with positive cardiovascular effects. However, due to their low bioavailability, metabolites are likely responsible for these properties. Recently, one of these metabolites, 4-methylcatechol, was described to be a very potent antiplatelet compound. This study aimed to compare its activity with its 22 close derivatives both of natural or synthetic origin in order to elucidate a potential structure-antiplatelet activity relationship. Blood from human volunteers was induced to aggregate by arachidonic acid (AA), collagen or thrombin, and plasma coagulation was also studied. Potential toxicity was tested on human erythrocytes as well as on a cancer cell line. Our results indicated that 17 out of the 22 compounds were very active at a concentration of 40 μM and, importantly, seven of them had an IC50 on AA-triggered aggregation below 3 μM. The effects of the most active compounds were confirmed on collagen-triggered aggregation too. None of the tested compounds was toxic toward erythrocytes at 50 μM and four compounds partly inhibited proliferation of breast cancer cell line at 100 μM but not at 10 μM. Additionally, none of the compounds had a significant effect on blood coagulation or thrombin-triggered aggregation. This study hence reports four phenol derivatives (4-ethylcatechol, 4-fluorocatechol, 2-methoxy-4-ethylphenol and 3-methylcatechol) suitable for future in vivo testing.
Keywords: fenol; fenoly; agregace trombocytů; Humans; Phenol; Phenols; aggregation; platelet; flavonoid; Platelet Aggregation Inhibitors; inhibitory agregace trombocytů; lidé; whole blood; Platelet Aggregation; catechol; Thrombin; trombin; 4-methylcatechol